2013
DOI: 10.1016/s1836-9553(13)70147-4
|View full text |Cite
|
Sign up to set email alerts
|

Do convolutions in Kinesio Taping matter? Comparison of two Kinesio Taping approaches in patients with chronic non-specific low back pain: protocol of a randomised trial

Abstract: RBR-7ggfkv. PROSPECTIVE REGISTRATION: Yes. FUNDED BY: Fundação de Amparo a Pesquisa do Estado de São Paulo (FAPESP), and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), Brazil. APPROVAL NUMBER: FAPESP number 2011/12926-0; CNPq number 470652/2011-0. ANTICIPATED COMPLETION: February 2013. CORRESPONDENCE: Leonardo Oliveira Pena Costa, Rua Cesário Galeno 448, Tatuapé, São Paulo/SP, Brazil 03071-000 Email: lcos3060@gmail.com FULL PROTOCOL: Available on the eAddenda at jop.physiotherapy.asn.au.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…In addition, in the literature it can be found that KT can increase the ROM, reduce swelling, inflammation, and bruising, enhance blood circulation, enhance strength and muscle tone, or be used in muscle spasms and cramping prevention and to speed recovery of overused muscles [ 32 – 34 , 37 – 42 ]. Most of the research is related to the use of KT in relieving pain, specifically reducing pain and disability in patients with chronic, nonspecific back pain [ 29 ]. It seems that KT can also be used to combat pain in patients with MTrPs [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the literature it can be found that KT can increase the ROM, reduce swelling, inflammation, and bruising, enhance blood circulation, enhance strength and muscle tone, or be used in muscle spasms and cramping prevention and to speed recovery of overused muscles [ 32 – 34 , 37 – 42 ]. Most of the research is related to the use of KT in relieving pain, specifically reducing pain and disability in patients with chronic, nonspecific back pain [ 29 ]. It seems that KT can also be used to combat pain in patients with MTrPs [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of results between the two forms of application, leads us to question the real effectiveness of varying the tension on the tape in the treatment of painful conditions. Several authors [2,6,19] have carried out studies comparing the effects of the use of KT in pain situations, such as chronic lumbar pain, acute neck whiplash sprains and medial epicondylitis; all compared the application of KT in two ways, one according to the recommendations of the technique, applying a tape tension of 20-50% that can cause the skin convolutions, which would be responsible for the technique's effects [1], and another where the tape was applied without tension. The results found corroborate ours and reveal that individuals treated with KT had a significant clinical improvement, regardless of the way it is applied, but without difference in results between the groups, supporting the idea that the effect of the tape is not related to the formation of skin convolutions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Kinesio Taping method, the tape application from origin to insertion with 10–15% of tension can facilitate muscle function and provide more support by increasing the sensory stimulation without performing the functional correction (mechanical support) [43]. Furthermore, also according to the method, applying the tape with the stretched muscle generates convolutions on the skin when the patient returns to neutral position, which can increase the sensory input [44]. The sham tape was placed similarly to the elastic tape with the patient in the same position.…”
Section: Methodsmentioning
confidence: 99%